A worth remembering Pepper Queen: Chēnnabhairādēvi - Pooja Naik (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
This research article aims to highlight the achievements of Queen Chēnnabhairādēvi who is unfamiliar to most people but worth remembering, ruled a small principality for a long time in a very commendable manner. She ruled the Sāḷuvas of Nagire (Honnāvar taluk in Uttara Kannada district) and Hāḍuvaḷḷi (taluk in Uttara Kannada district) principalities unitedly. Her achievements have been assessed by examining primary sources such as inscriptions, Portuguese accounts, works of court poets, and secondary sources. Examined sources show that her political struggles, commercial policies, cultural advancements, and conflict with the Portuguese made her one of the finest queens of Karnataka and India has ever seen. Portuguese addressed her ‘‘Reyna da Pimenta’’, the pepper queen.